Pengaruh Lingkungan Kerja dan Pelatihan Terhadap Kinerja Karyawan Balai Pengelola Transportasi Darat Kelas Ii Banten - Samsu Rijal; Djaka Adiwinata; Mira Nurhikmat (Universitas 45 Surabaya, 2025)
Every organization or company has various important parts to support the running of the organization's or company's activities in achieving organizational or company goals. This research aims to determine the influence of the work environment, training and employee performance. This research used a sample of 80 respondents. The research method used is causality research. To answer the hypothesis using Structured Equation Model (SEM) data analysis using PLS (Partial Least Square). Based on the testing, the results showed that the work environment and training had a positive and significant effect, both partially and simultaneously.